DESIGN, OPTIMIZATION, AND EVALUATION OF IBUPROFEN FAST-DISSOLVING TABLETS EMPLOYING STARCH VALERATE – A NOVEL SUPER DISINTEGRANT - KUMAR RADA, ANTHOSH; M, RAMYA; KANDUKURI, SHAMBHAVI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The main aim is to design, optimize, and evaluate ibuprofen fast-dissolving tablets by employing starch valerate-A novel super disintegrant. Methods: The fast-dissolving tablet of ibuprofen was prepared by employing starch valerate as super disintegrant in different proportions in each case by direct compression method using 23 factorial design, sodium starch glycolate, and crospovidone used as super disintegrants. In the 23 factorial design, these super disintegrants were applied to investigate the interaction effects of three variables, that is, (a) starch valerate, (b) sodium starch glycolate, and (c) crospovidone. The drug content, hardness, friability, disintegration time, and other dissolution characteristics were determined. Results: The starch valerate prepared was found to be fine, free-flowing, slightly crystalline powder. Starch xanthate exhibited good swelling in water with 125.2%. All the fast-dissolving tablets formulated employing starch valerate were of good quality with regard to drug content (100±5%), hardness (3.6–3.8 kg/sq. cm), and friability (0.11-0.12%). The disintegration time of all the formulated tablets was found to be in the range of 12±0.02 to 30±0.02s. The optimized formulation FL8 has the least disintegration time, that is, 12±0. 02s. The in vitro wetting time of the formulated tablets was found to be in the range of 21±0.09 to 44±0.10s. The in-vitro wetting time was less (i.e., 90s) in optimized formulation FL8. The water absorption ratio of the formulated tablets was found to be in the range of 30±0.12 to 100±0.09%. Conclusion: Starch valerate was found to be a super disintegrant which enhanced the dissolution efficiency when combined with sodium starch glycolate, crospovidone, with the ibuprofen.